UI/UX Research & Design Aplikasi E-commerce: Fixup Waste With Design Thinking Methode - Daffa Aidhil Fitra; Dewi Ayu Nur Wulandari; Helina Apriyani (JURNAL TEKNIK KOMPUTER AMIK BSI, 2024)
The problem of waste and unused waste has reached an alarming level, where it has become the main focus for the government. This problem raises special concern because the number of waste production continues every year. The reason is the consumptive lifestyle of new products that are trending among the public. It is this consumptive lifestyle that causes many items that were previously owned by individuals to be wasted, most of them even end up in landfills or the sale of used goods, without any guarantee that these items can be recycled into new products. To overcome this problem, innovation is needed in the form of digital products such as e-commerce applications and websites. This innovation serves as a platform to promote trending items and invites the public to avoid excessive consumption patterns of these products through the offered Upcycling Products. The process of developing this digital product uses the Design Thinking method, which places a focus on the needs and problems faced by current users. The stages in this method start from Emphatize (understand the user), Define (define the problem), Ideate (ideate), Prototype (prototype), and Testing (conducting tests on users). Each stage is carried out repeatedly to ensure optimal results for users. The end result of this design process is the E-commerce application prototype design and the Fixup Waste website.